Internalisasi Nilai-Nilai Pancasila terhadap Pengaturan Hak Pengelolaan Atas Tanah - Sofia Rahmawati (AGRIFITIA : Journal of Agribusiness Plantation, 2023)
Management rights on Land (HPL) is right outside in Act. No. 5 of 1960 on Basic Regulation on Agrarian Principles (UUPA). Management rights on Land (HPL) are state control rights whose implementation authority is partly delegated to management rights on land (HPL) holders. UUPA does not regulate about Management Rights on Land (HPL) which causes problems both in the realm of regulation and practice which creates confusion, chaos and does not reflect justice as the value of the fifth principal of Pancasila. The writing of this law uses a normative-juridical method, using primary legal materials, and secondary legal materials. In practice, initially there was a tendency for Management right on Land (HPL) to only be intended for the "strong economy" or investors and negated the "weak economy" group such as customary law communities. Government Regulation No. 18 of 2021 on Right to Manage, Land Rights, Multi Story Housing Units and Land Registration which is the latest legal basis for management rights on land (HPL) emphasizes the basic principles of management rights on Land (HPL) which are expected to provide justice, especially for the "weak economy" group in the context of improving their standard of living and management rights on land (HPL) will not in fact become a source of agrarian conflicts in the future.